Studies on seed transmission of Xanthomonas campestris pv phaseoli in common beans in Uganda - Opio, A.F.; Allen, David J.; Teri, J.M. (1993)
Studies on the seed transmission of Xanthomonas campestris PV phaseoli check for this species in other resources (XCP) that cause common and fuscous blight of beans were conducted in Uganda. Bean seed was the main source of primary inoculum. The population of XCP in farmers', commercial and research seeds averaged 105 109 colony forming units (cfu) per 100 seeds; the levels of seed infection were 0.3-16.1%. There was a positive correlation between seed symptoms and population of XCP per seed. However, where seed was either slightly diseased or symptomless, XCP did not decrease bean germination irrespective of population density. The minimum population of XCP required to initiate infection in the field was 102 cfu per seed while 0.2% seed infection level resulted in serious disease incidence.